Activities of the Mathematical Society in 2002–2004 - Kubilius, Jonas (Lietuvos matematikos rinkinys, 2004)
The article gives a survey of activities of the Mathematical Society during last three years. Some problems of the mathematical life in Lithuania are rised.
Keywords: Lithuanian Mathematical Society